Disrupting Diagnostic Reasoning. (April 2015) - Monteiro, Sandra D.; Sherbino, Jonathan David; Ilgen, Jonathan Seth; Dore, Kelly L.; Wood, Timothy J.; Young, Meredith E.; Bandiera, Glen; Blouin, Danielle; Gaissmaier, Wolfgang; Norman, Geoffrey R.; Howey, Elizabeth
<x xml:space="preserve">Abstract</x> Purpose Others have suggested that increased time pressure, sometimes caused by interruptions, may result in increased diagnostic errors. The authors previously found, however, that increased time pressure alone does not result in increased errors, but they did not test the effect of interruptions. It is unclear whether experience modulates the combined effects of time pressure and interruptions. This study investigated whether increased time pressure, interruptions, and experience level affect diagnostic accuracy and response time. Method In October 2012, 152 residents were recruited at five Medical Council of Canada Qualifying Examination Part II test sites. Forty-six emergency physicians were recruited from one Canadian and one U.S. academic health center. Participants diagnosed 20 written general medicine cases. They were randomly assigned to receive fast (time pressure) or slow condition instructions. Visual and auditory case interruptions were manipulated as a within-subject factor. Results Diagnostic accuracy was not affected by interruptions or time pressure but was related to experience level: Emergency physicians were more accurate (71%) than residents (43%) (F = 234.0, P < .0001) and responded more quickly (54 seconds) than residents (65 seconds) (F = 9.0, P < .005). Response time was shorter for participants in the fast condition (55 seconds) than in the slow condition (73 seconds) (F = 22.2, P < .0001). Interruptions added about 8 seconds to response time. Conclusions Experienced emergency physicians were both faster and more accurate than residents. Instructions to proceed quickly and interruptions had a small effect on response time but no effect on accuracy.